Current perspectives on child language acquisition : how children use their environment to learn - Rowland, Caroline, 1971-; Theakston, Anna L.; Ambridge, Ben, 1977-; Twomey, Katherine (Katherine Elizabeth); Lieven, Elena V. M. (Trends in language acquisition research, 2020)
"In recent years there has been an increasing realisation that the full complexity of language acquisition demands theories that (a) explain how children integrate information from multiple sources in the environment, (b) build linguistic representations at a number of different levels, and (c) learn how to combine these representations in order to communicate effectively. These new findings have stimulated new theoretical perspectives that are more centered on explaining learning as a complex dynamic interaction between the child and her environment. This book is the first attempt to bring these new theoretical perspectives together in one place. It is a collection of essays written by a group of researchers who all take an approach centered on child-environment interaction, and all of whom have been influenced by the work of Elena Lieven, to whom this collection is dedicated"--